Analysis of an N-terminal deletion in subunit a of the Escherichia coli ATP synthase - Ishmukhametov, Robert R. (J Bioenerg Biomembr, 2017)
Subunit a is a membrane-bound stator subunit of the ATP synthase and is essential for proton translocation. The N-terminus of subunit a in E. coli is localized to the periplasm, and contains a sequence motif that is conserved among some bacteria. Previous work has identified mutations in this region that impair enzyme activity. Here, an internal deletion was constructed in subunit a in which residues 6–20 were replaced by a single lysine residue, and this mutant was unable to grow on succinate minimal medium. Membrane vesicles prepared from this mutant lacked ATP synthesis and ATP-driven proton translocation, even though immunoblots showed a significant level of subunit a. Similar results were obtained after purification and reconstitution of the mutant ATP synthase into liposomes. The location of subunit a with respect to its neighboring subunits b and c was probed by introducing cysteine substitutions that were known to promote cross-linking: a_L207C + c_I55C, a_L121C + b_N4C, and a_T107C + b_V18C. The last pair was unable to form cross-links in the background of the deletion mutant. The results indicate that loss of the N-terminal region of subunit a does not generally disrupt its structure, but does alter interactions with subunit b.